The heads of religious houses, England and Wales. - Smith, David M.; London, Vera C. (Cambridge University Press, 2001)
This book is a continuation of The Heads of Religious Houses: England and Wales 940–1216, edited by David Knowles, C. N. L. Brooke and Vera London, which itself is reissued with substantial addenda by Professor Brooke. This present volume continues the lists from 1216 to 1377. In this period further record sources have been provided by episcopal registers, governmental enrolments, court records, and so on. Full references are given for establishing the dates and outline of the career of each abbot or prior, abbess or prioress, when known. The lists are arranged by order: the Benedictine houses (independent, dependencies and alien priories); the Cluniacs; the Grandmontines; the Cistercians; the Carthusians; the Augustinian canons; the Premonstratensians; the Gilbertine order; the Trinitarian houses; the Bonhommes; and the nuns. An introduction discusses the nature, use and history of the lists and examines critically the sources on which they are based.